Activation of ventral CA1 hippocampal neurons projecting to the lateral septum during feeding. Issue 3 (9th December 2020) - Kosugi, Kenzo; Yoshida, Keitaro; Suzuki, Toru; Kobayashi, Kenta; Yoshida, Kazunari; Mimura, Masaru; Tanaka, Kenji F.
Abstract: A number of studies have reported the involvement of the ventral hippocampus (vHip) and the lateral septum (LS) in negative emotional responses. Besides these well‐documented functions, they are also thought to control feeding behavior. In particular, optogenetic and pharmacogenetic interventions to LS‐projecting vHip neurons have demonstrated that the vHip →LS neural circuit exerts an inhibition on feeding behavior. However, there have been no reports of vHip neuronal activity during feeding. Here, we focused on LS‐projecting vCA1 neurons (vCA1 →LS ) and monitored their activity during feeding behaviors in mice. vCA1 →LS neurons were retrogradely labeled with adeno‐associated virus carrying a ratiometric Ca 2+ indicator and measured compound Ca 2+ dynamics by fiber photometry. We first examined vCA1 →LS activity in random food‐exploring behavior and found that vCA1 →LS activation seemed to coincide with food intake; however, our ability to visually confirm this during freely moving behaviors was not sufficiently reliable. We next examined vCA1 →LS activity in a goal‐directed, food‐seeking lever‐press task which temporally divided the mouse state into preparatory, effort, and consummatory phases. We observed vCA1 →LS activation in the postprandial period during the consummatory phase. Such timing‐ and pathway‐specific activation was not observed from pan‐vCA1 neurons. In contrast, reward omission eliminated this activity, indicating that vCA1 →LS activation is contingent on the food reward. Sated mice pressed the lever significantly fewer times but still ate food; however, vCA1 →LS neurons were not activated, suggesting that vCA1 →LS neurons did not respond to habitual behavior. Combined, these results suggest that gastrointestinal interoception rather than food‐intake motions or external sensations are likely to coincide with vCA1 →LS activity. Accordingly, we propose that vCA1 →LS neurons discriminate between matched or unmatched predictive bodily states in which incoming food will satisfy an appetite. We also demonstrate that vCA1 →LS neurons are activated in aversive/anxious situations in an elevated plus maze and tail suspension test. Future behavioral tests utilizing anxious conflict and food intake may reconcile the multiple functions of vCA1 →LS neurons.